Ultrassonografia Doppler na avaliação renal de cadelas diagnosticadas com piometra antes e após tratamento com ovariosalpingohisterectomia - Santos, Roberta V. [UNESP]; Merlini, Natalie B. [UNESP]; Souza, Livia P. [UNESP]; Machado, Vânia M.V. [UNESP]; de Figueiredo Pantoja, José Carlos [UNESP]; Prestes, Nereu Carlos [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of this study was evaluate the renal hemodynamics of bitches with pyometra by means of laboratory tests, ultrasound B mode and Doppler, before and after treatment with ovariohysterectomy (OSH). This study evaluated 30 bitches with pyometra, all were subjected to OSH (moment 1) and 20 were evaluated after 7 days (moment 2). The renal perfusion, the resistivity index (RI) of the main renal artery and the interlobar arteries (cranial, middle and caudal) were statistically different between times 1 and 2 (p<0,05). There was no statistical difference for renal perfusion between the left and the right kidney at the time 1 and 2. The correlations between the IR of the main artery and the variables used to determine renal function were stablished at the time 1. For the correlated variables: urea, creatinine, proteinuria, ratio GGT/creatinine and protein/creatinine were curvilinear and positive associations with the resistivity index of the main renal artery (p<0,05), however these correlations were considered medium and weak. Comparing the RI of the main renal artery with different scores of dehydration and renal perfusion, there was statistical difference, and show increased of resistance renal in bitches with moderate reduction in renal perfusion as well as in dehydrated bitches. Were evaluated several features of renal morphology in ultrasound B mode, however, only the presence of pelvic dilatation, medullary signal and other changes as infarcts areas and diffuse hyperechoic spots in the renal cortical and medullary were statistically different from one moment to the other, most frequently at the time 2. The results of this study show that the Doppler ultrasound can identify changes of reduction in renal perfusion by color Doppler and the increasing of the resistivity index of the renal arteries in some bitches with pyometra. As well as, the ultrasound B mode, although has non-specific changes, can detect progressive renal disorders in bitches with pyometra.
Doppler ultrasonography in the renal evaluation of bitches diagnosed with pyometra before and after treatment with ovariohysterectomy
Keywords: Bitches; Pyometra; Renal Doppler; Ultrasonography B mode